Pengaruh Pelayanan Keluhan Pelanggan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Melalui ACPI PT. Pos Indonesia (Persero) Cabang Padang - Febsri Susanti; Dea Edgina (Indonesian Journal of Applied Accounting and Finance, 2021)
As the oldest logistics company in Indonesia, PT. Pos Indonesia (Persero) should be able to win the hearts of customers, but there are still many customers who complain about the services provided by this company. This study aims to examine the effect of the customer complaint service variable and customer satisfaction variable on the customer loyalty variable through ACPI PT. Pos Indonesia Padang Branch. The data collection method was carried out by distributing questionnaires with a sample of 96 respondents. The type of research is quantitative research. The data analysis technique used is multiple linear regressions using the SPSS 16.0 program. The results of this study indicate that customer complaint service does not directly affect customer loyalty at PT. Pos Indonesia, Padang Branch while customer satisfaction has a direct effect on customer loyalty.